Rural development in the United States connecting theory, practice, and possibilities - Galston, William A. 1947-; Baehler, Karen J. (Island Press, 1995)
Rural Development in the United States presents a comprehensive evaluation of the economic, environmental, and political implications of past rural development and a thorough consideration of the directions in which future development efforts should go. The authors have assembled the best of what is being thought and done with regard to rural development in the United States, and they place it in a broad theoretical, historical, and geographical context